Menginspirasi Dan Memotivasi: Mengubah Gaya Kepemimpinan Di PCNU Sidoarjo - Fathya Jihan Natasya; Afifatus Solikhah; Tutie Azzahra; Anala Ilfi Xena Andini; Fransisca Eri Yulianti; Muhammad Jamaludin Fuadi; Muhammad Farly Rizky (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
Leadership is the ability to constructively influence others in running a business. Effective leadership style not only includes managerial skills, but also the ability to inspire and motivate people around them, especially in PCNU Sidoarjo. This study uses a quantitative descriptive method, the population in this study is the MWCNU board in 18 sub-districts in Sidoarjo district with an average population of 60 people, as for ease in collecting the data taken, then the determination of the sample in the study. In this study the authors used purposive sampling technique, namely sampling with certain considerations, determining the sample size using the Solvin formula and found a sample of 53 respondents. The results of the research found that (1) Inspire has a positive and significant effect on Leadership Style at PCNU Sidoarjo. (2) Motivate has a positive and significant effect on Leadership Style at PCNU Sidoarjo.